2017
DOI: 10.1371/journal.pone.0185635
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of congenital cytomegalovirus (cCMV) among physical and occupational therapists in the United States

Abstract: Congenital cytomegalovirus (cCMV) infections cause more children to have permanent disabilities than Down Syndrome, Fetal Alcohol Syndrome, Spina Bifida, and pediatric HIV/AIDS combined. The risk of infection during pregnancy can be significantly decreased using universal precautions, such as thorough handwashing and cleansing of surfaces and objects that have come into contact with infected body fluids. Children under 3 years of age are commonly asymptomatic excretors of CMV, with the highest viral loads pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 77 publications
1
20
0
1
Order By: Relevance
“…Regional studies conducted in North America (26,27) have shown that neonates born in more deprived households are at higher likelihood to develop cCMV, a finding also supported by this study. Surveys of paediatric healthcare practitioners in France and USA show that less than half of respondents had adequate knowledge of the disease to educate women during pregnancy (28,29). These data should encourage healthcare practitioners to reinforce important antenatal hygiene measures.…”
Section: Discussionmentioning
confidence: 98%
“…Regional studies conducted in North America (26,27) have shown that neonates born in more deprived households are at higher likelihood to develop cCMV, a finding also supported by this study. Surveys of paediatric healthcare practitioners in France and USA show that less than half of respondents had adequate knowledge of the disease to educate women during pregnancy (28,29). These data should encourage healthcare practitioners to reinforce important antenatal hygiene measures.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the lack of cCMV knowledge common throughout general society, surveys of various healthcare professionals around the world also indicate a gap in both awareness and in knowledge of cCMV. [19][20][21][22][23][24] An important next step is addressing gaps in provider knowledge given that women are likely to learn about cCMV from their providers. Implementing regular educational sessions for healthcare providers, such as through national boards and major meetings, is important, as suggested by Dedhia et al 25 There are limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Чаще нарушения слуха выявляются уже за пределами периода новорожденности: они могут прогрессировать, периодически уменьшаться или сочетаться с вестибуляр-ными нарушениями [17]. Надежных критериев прогноза развития отдаленных нарушений слуха у детей как при манифестной и тяжелой, так и при латентной ЦМВИ пока не существует.…”
Section: педиатрическая фармакологияunclassified